Incidence and Haematological Changes in Haemoprotozoan Infections in Bovines of South Gujarat - Patel, MD; Kumar, Niranjan; Tyagi, KK; Sorthiya, LM (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was conducted to record the incidence, risk factors and haematological changes during haemoprotozoan infections of bovines over a period from January, 2014 to December, 2016. A total of 193 suspected cases (141 cattle and 52 buffaloes) presented at Teaching Veterinary Clinical Complex and Livestock Research Station, Navsari Agricultural University, Navsari, Gujarat, were examined for the presence of haemoprotozoan parasites by Giemsa staining technique. Total 46 (23.83%) cases (23 each of cattle and buffaloes) were found positive for presence of haemo parasite infection. The effect of source of sample, season and species on incidence of haemo prasitic infections was significant whereas effect of year was non-significant. Higher incidence was observed in rainy (34.92) followed by winter (25.42 %) and summer (12.68%) season. Significantly higher incidence of Anaplasmosis (8.29%) was observed followed by Babesiosis (6.74%), Theileriosis (3.63%) and Trypanosomosis and Ehrlichiosis (2.59% each). All positive cases showed comparatively lower values of haemoglobin (Hb.), packed cell volume (PCV) and total erythrocyte count (TEC) whereas values of total leukocyte count (TLC) and differential leukocyte count (DLC) were within the normal range.